(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
This paper will analyze the geopolitical visions of Russia and the United States concerning the People’s Republic of China. The analysis was made following the historical context of the political relations between China and Russia, and China and the U.S. The states that are visible show that Russia and the U.S., through the assumed engagements and developed positions on the Asian continent, are establishing rapprochement with China. This practical geopolitical approach of both Russia and the U.S., according to China, does not correlate with a formal geopolitical approach to the analysis of their relationship. This paper portrays the geopolitical vision of the relations between Russia and China, in terms of practical and formal geopolitics, elaborated by the theory of “The Fall of China” by Alexander Dugin. The same approach is applied to the geopolitical visions of the United States for China, entitled “Strategy for Containment” by the geopolitical analyses of Zbigniew Brzezinski and the practical geopolitical actions of the current U.S. administration.